2017
DOI: 10.1016/j.heliyon.2017.e00266
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective function of the sterol regulatory element binding factor 1–fatty acid desaturase 1/2 axis in early-stage age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the most common cause of vision loss in elderly individuals throughout the developed world. Inhibitors of vascular endothelial growth factor have been successfully used to treat choroidal neovascularization in late-stage AMD. The pathogenesis of early-stage AMD, however, remains largely unknown, impairing efforts to develop effective therapies that prevent progression to late-stage AMD. To address this, we performed comparative transcriptomics of macular and extramacul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 66 publications
2
8
0
Order By: Relevance
“…Tenascin C, the most statistically significant differentially expressed gene in this pathway, can upregulate TGFβ and promote inflammatory processes (Reinhard et al, 2017), in line with the increased level of Tenascin C identified in surgically excised choroidal neovascular membranes (Nicolò et al, 2000) and observation of its secretion in neovascular AMD (Kobayashi et al, 2016;Reinhard et al, 2017). Furthermore, although the fatty acid metabolism pathway was not found to be statistically significantly associated with AMD in our analysis, the finding that all differentially expressed genes in this pathway were found exclusively in macular RPE/choroid underlines the geographical differences in gene expression patterns between macular and non-macular RPE/choroid regions, previously suggested by Whitmore et al (2014) and Ashikawa et al (2017). Specific examples of genes with a macular pattern of differential expression were Fatty Acid Desaturase 1 (FADS1) and Fatty Acid Desaturase 2 (FADS2), genes encoding delta-5 and delta-6 desaturases, implicated in drusen formation in a recent study (Ashikawa et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
“…Tenascin C, the most statistically significant differentially expressed gene in this pathway, can upregulate TGFβ and promote inflammatory processes (Reinhard et al, 2017), in line with the increased level of Tenascin C identified in surgically excised choroidal neovascular membranes (Nicolò et al, 2000) and observation of its secretion in neovascular AMD (Kobayashi et al, 2016;Reinhard et al, 2017). Furthermore, although the fatty acid metabolism pathway was not found to be statistically significantly associated with AMD in our analysis, the finding that all differentially expressed genes in this pathway were found exclusively in macular RPE/choroid underlines the geographical differences in gene expression patterns between macular and non-macular RPE/choroid regions, previously suggested by Whitmore et al (2014) and Ashikawa et al (2017). Specific examples of genes with a macular pattern of differential expression were Fatty Acid Desaturase 1 (FADS1) and Fatty Acid Desaturase 2 (FADS2), genes encoding delta-5 and delta-6 desaturases, implicated in drusen formation in a recent study (Ashikawa et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
“…Forcing fRPE cells to rely on oxidation of glutamine, the most abundant free amino acid in blood, caused upregulation of genes involved in the synthesis of cholesterol, monounsaturated and polyunsaturated fatty acids, as well as genes associated with lipid import. Transcripts for three of the upregulated genes (FADS1, FADS2, and ACAT2) are increased in macular but not extramacular RPE from individuals with early-stage AMD 73 .…”
Section: Discussionmentioning
confidence: 92%
“…The solution was injected into 1-cell-stage zebrafish embryos derived from the Tg (eno2: cerulean) line. At 4 months post-fertilization, genomic DNA was extracted from the fins of F0 zebrafish and used to detect CRISPR/Cas9-induced mutations according to previous reports [59,60] with some modifications as follows. A short fragment of the c3orf70a or c3orf70b gene encompassing the target sites was amplified from genomic DNA using the primers shown in Supplemental Table S3.…”
Section: Generation Of C3orf70-ko Zebrafishmentioning
confidence: 99%
“…A short fragment of the c3orf70a or c3orf70b gene encompassing the target sites was amplified from genomic DNA using the primers shown in Supplemental Table S3. Three-step PCR was carried out using 40 cycles of 94 • C for 30 s, 60 • C for 30 s, and 68 • C for 30 s. The PCR products were electrophoresed in 10% polyacrylamide gels as described previously [59,60] and F0 fish in which the CRISPR/Cas9-induced mutation was present were crossed with the Tg(eno2: Cerulean) zebrafish line to obtain F1 progeny (c3orf70a+/-:c3orf70b+/+ or c3orf70a+/+:c3orf70b+/-). The F1 generation was reared and screened for the presence of the mutation by PCR, as described above.…”
Section: Generation Of C3orf70-ko Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation